2013
DOI: 10.3390/toxics2010001
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Metals in Hair in Childhood: Preliminary Associations with Neuropsychological Behaviors

Abstract: For more than 100 years, an electrochemical plant has been operating in Flix (Catalonia, Spain) by the Ebro River. Its activities have originated a severe accumulation of environmental contaminants (metals, organochlorinated pesticides and radionuclides) in sediments of the Flix reservoir, while mercury (Hg) has been also frequently released to the air. Environmental exposure to industrial pollutants has been associated with decreased intelligence and behavioral problems. In the present study, we assessed, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Furthermore, despite the mean Cr concentration is similar to most levels found in recent literature, Cr concentrations in the urban area of Madrid were approximately 5-fold higher than those of the present study [46]. The mean level of Hg was also higher than the concentrations found in other locations, such as toxic waste disposal sites of Russia [35] and different urban areas [14,47]. In contrast, Hg concentrations in children from Tarragona County were lower than those found in other Spanish studies focused on assessing urban and industrial/mining areas [26,46].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, despite the mean Cr concentration is similar to most levels found in recent literature, Cr concentrations in the urban area of Madrid were approximately 5-fold higher than those of the present study [46]. The mean level of Hg was also higher than the concentrations found in other locations, such as toxic waste disposal sites of Russia [35] and different urban areas [14,47]. In contrast, Hg concentrations in children from Tarragona County were lower than those found in other Spanish studies focused on assessing urban and industrial/mining areas [26,46].…”
Section: Discussionsupporting
confidence: 71%
“…In contrast, higher Ni levels were found when our data are compared with those of other studies, excepting those reported by Xie et al [30] in Shaoguan Guangdong (China) and Evrenoglou et al [14] in Athens (Greece). In turn, Pb levels were higher than those found in hair of children living in some mining, volcanic, sub-urban and urban areas [14,26,34,36,47] but lower than values from children living near certain mining zones, as well as near to toxic waste disposal sites and cement plants [11,30,34,35,37]. The individual characteristics of the geographic areas where the children live would probably be the responsible of the observed variability in Ni and Pb levels among studies.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The adult donors may be exposed to a variety of substances, including HMs from either environmental or occupational sources [ 23 ]. Neonates are one of the most vulnerable groups to such exposures because they are the most frequent recipients of transfused blood [ 24 , 25 , 26 ]. Safe levels for intravenous administration of these metals are unknown [ 3 ].…”
Section: Introductionmentioning
confidence: 99%